1994
DOI: 10.1103/physrevlett.73.1990
|View full text |Cite
|
Sign up to set email alerts
|

Space-Time Observation of an Electron Gas in SiO2

Abstract: We report the first space-time observation of the ultrafast excitation and relaxation of an electron gas pumped into the conduction band of a wide band-gap insulator by an intense subpicosecond laser pulse. The experiment is based on a new phase-sensitive technique which allows a resolution of 120 fs in time and 5~i,m in space. In crystalline and amorphous Si02, no evidence of gas expansion has been observed and a mean trapping time of 150 fs for the photogenerated carriers is measured. PACS numbers: 78.47.+p,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
121
2
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(140 citation statements)
references
References 15 publications
11
121
2
6
Order By: Relevance
“…In fused silica, a material of technological interest and thoroughly investigated, several particular physical manifestations were observed. Saeta et al [5] and Audebert et al [6] indicated more than a decade ago a characteristic fast sub-ps relaxation channel for excited carriers in self-induced lattice distortions with the formation of self-trapped excitonic (STE) states and their conversion to Frenkel pairs (nonbridging oxygen and E centers). This is indicative for a still rigid matrix, whereas as the level of excitation increases, the relaxation times become long, suggesting a decrease in the trapping capacity, consequence of vibrational molecular activity in low viscosity phases [7] .…”
Section: Introductionmentioning
confidence: 99%
“…In fused silica, a material of technological interest and thoroughly investigated, several particular physical manifestations were observed. Saeta et al [5] and Audebert et al [6] indicated more than a decade ago a characteristic fast sub-ps relaxation channel for excited carriers in self-induced lattice distortions with the formation of self-trapped excitonic (STE) states and their conversion to Frenkel pairs (nonbridging oxygen and E centers). This is indicative for a still rigid matrix, whereas as the level of excitation increases, the relaxation times become long, suggesting a decrease in the trapping capacity, consequence of vibrational molecular activity in low viscosity phases [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Although we do not know the parameters directly, there are some hints. For example, elegant experiments 11 have shown the lifetime of conduction band electrons in fused silica to be about 1 ps and we assume that value here. The pump-probe experiments suggest a lifetime τ 1 on the order of 1 ns and that is also assumed.…”
Section: Multi-level Modelmentioning
confidence: 99%
“…hoton ionization rate W MPI ∝ I 6 figure shows Keldysh's theory dotted line), and six photon abection for inverse bremsstrahlung ( 9 ) where the momentum transfer collision time τ c = 2.33×10 -14 s. In the third term on RHS of Eq. (7), τ r denotes electron recombination with a characteristic time of τ r = 150 fs for fused silica (19) . Although τ r is reported to depend on electric field, it is treated as a constant value in this paper.…”
Section: Theorymentioning
confidence: 99%